Methodology for assessing the risk of incidents during passenger road transportation using the functional resonance analysis method - Oleg Bazaluk; Larysa Koriashkina; Serhii Cheberiachko; Oleg Deryugin; Mykola Odnovol; Vasyl Lozynskyi; Olha Nesterova (Heliyon, 2022)
Safety of passenger road transportation (PRT) is a global problem considered by scientists. The present study is aimed at PRT safety improvement by developing its advanced model with accident risk minimization. Functional Resonance Analysis Method is used to identify factors influencing PRT safety. Accident risk assessment of the combined action of several factors in PRT is based on a phenomenological model. Possible good and bad PRT scenarios were considered differing in the staff professional experience, work shift duration, speed, vehicle service lifetime, and driver's stress load. Method for quantitative assessment of five main functions in PRT with their variability caused by parameters changes was designed. The proposed criteria were used to assess the parameter's deviations from their normative values and determine the major characteristics of each function. The recommendations for monitoring the driver's psychophysiological state at all transportation stages were developed and the relationship of transportation functions characteristics and criteria affecting passenger safety was established. This methodology enables assessing the PRT reliability level at a certain time. The approach allows evaluating the criteria affecting traffic safety, identifying their potential functionally resonant effect for abnormal PRT due to conditional changes; developing mechanisms to reduce accident risks by improving technical and organizational management.